Oncoplastic and reconstructive breast surgery - Wignarajah, Primeera; Malata, Charles M.; Benson, John R. (Frontiers in Oncology, 2023)
Oncoplastic breast surgery is the standard of care in many Breast units across the world. The evolution and continued pioneering improvements in this field are summarised in this article. An overview of oncoplastic and reconstructive procedures for breast cancer is given encompassing the nuances that arise with multimodality treatments for breast cancer. The holistic care of the patient is central in any breast cancer surgery and continued efforts are made to assess patient reported outcome measures and act on their findings to improve the outcomes, care and experience for patients.